First evidence of breeding and eastward range expansion of the Mediterranean short-toed lark (Alaudala rufescens) in King Abdulaziz Royal Reserve, Saudi Arabia - HAZEM ABDULLAH AL-ASMARI; ABDELWAHAB CHEDAD; ABDULAZIZ MUBARAK AL-QAHTANI; NUWAYYIR MOHAMMAD ALSHAMMARI; MOHAMMED HAMED ALTALHI; ABDULRAHAMAN SALEM ALZAHRANI; HUSSEIN H. ALKHAMIS; ABDULLAH MOHAMMED ALOWAIFEER; ABDULWAHED FAHAD ALREFAEI (Society for Indonesian Biodiversity, 2025)
Abstract. Al-Asmari HA, Chedad A, Al-Qahtani AM, Alshammari NM, Altalhi MH, Alzahrani AS, Alkhamis HH, Alowaifeer AM, Alrefaei AF. 2025. First evidence of breeding and eastward range expansion of the Mediterranean short-toed lark (Alaudala rufescens) in King Abdulaziz Royal Reserve, Saudi Arabia. Biodiversitas 26: 4048-4056. We report the first confirmed breeding records of the Mediterranean short-toed lark (Alaudala rufescens) in the King Abdulaziz Royal Reserve (KARR), eastern Saudi Arabia. Field surveys conducted during the winter and spring of 2025 documented territorial pairs and fledglings, indicating successful local reproduction. Based on observed chick development and known incubation and fledging periods, egg-laying likely began in mid-March, with juveniles still present in late May, suggesting a prolonged breeding period under favorable spring conditions. This represents a notable eastward expansion of the species' known breeding range, previously limited to western and northern Saudi Arabia, and may drive by ecological or climatic factors such as increased aridity tolerance or changes in habitat availability. Seasonal monitoring revealed high winter abundance (2,387 individuals) followed by a marked decline in spring (296), including an estimated 90 breeding pairs, 45 juveniles, and 70 fledglings, highlighting both temporal dynamics and the effectiveness of mobile transects in detecting desert bird populations. The species displayed notable trophic flexibility: while nestlings fed primarily on soft-bodied invertebrates, adults consumed a broader omnivorous diet including insects and plant matter. These results illustrate the ecological adaptability of A. rufescens and emphasize the importance of continued monitoring in arid environments to track range shifts and inform conservation strategies. Additionally, our study confirms the presence of a resident breeding population in the northern sector of the King Abdulaziz Royal Reserve, coexisting with a winter migratory group.